Kekuasaan Pemerintah dalam Menangani Kekeringan di Kecamatan Sabu Liae, Kabupaten Sabu Raijua Ditinjau dari Undang-Undang Nomor 17 Tahun 2019 Tentang Sumber Daya Air - Lepa Avrilianti Putri Mone Mira; Hernimus Ratu Udju; Cyrilius W. T. Lamataro (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
This research aims (1) to find out the regulation of the authority of the Sabu Raijua Regency Government in dealing with drought, and (2) to find out the government's efforts in dealing with drought in Sabu Raijua Regency. and (3) to find out the factors that hinder government efforts in dealing with drought in Sabu Liae District, Sabu Raijua Regency. This research uses a normative juridical approach and is supported by empiricial juridicial research. Data collection techniques in this study are interview data collection, and literature study, and analyzing data descriptively and perspectively. The results of the study indicate that (1) Sabu Raijua Regency has the authority to set policies according to its territory, so it is necessary to set policies in dealing with drought, the policies needed to deal with drought include various elements that can help better manage water resources and reduce the impact of drought so that there is no clean water crisis, in this case it must include various initiatives and actions, depending on local conditions and problems faced. (2) Efforts made by the government in dealing with drought in Sabu Raijua Regency include: reforestation programs, extension programs, reservoir construction programs, and clean water distribution programs. (3) Factors that hinder government efforts in dealing with drought in Sabu Liae District, Sabu Raijua Regency include several factors, namely community legal awareness, cost factors, and facility factors. Based on the results of the research, it is hoped that the Sabu Raijua Regency government can be more reactive and proactive in making policies governing water resources by making local regulations on water resources in mitigating and adapting to climate change, including soil and water conservation programs.